Application of Software Methods for Automated Processing of Sources of Personal Origin - Prigodich, Nikita Dmitrievich; Korobko, Semen Sergeevich (Историческая информатика, 2023)
The subject of this research is software methods of automated preprocessing of historical sources and the development of effective solutions to problems when working with sources of personal origin. The article analyzes the current situation in the use of modern software methods. The authors demonstrate the main range of arguments for which such historical sources from a technical point of view should be considered separately. A methodological analysis of the features of the application of optical character recognition based on preprocessed data is carried out. Special attention is paid to the advantages and key parameters of the effectiveness of the final result of work when using automated text processing, including the further use of OCR methods. The scientific novelty of the research lies in the proposal and detailed description of a software solution to the current problem based on machine learning methods. The developed program has three phases of working with digital copies of sources of personal origin. It is based on the use of the OpenCV library and solving a number of problems using the Hough transform. Based on the general analysis of the study, we can highlight the main advantages of automated preprocessing of scanned documents: reducing time, improving accuracy, combating distortion and optimizing the process. The presented results of successful testing of the developed solution allow us to judge the possible areas of its effective application.